Upaya Pemantauan Keluhan Kardiorespirasi Oleh Keluarga Dengan Kejadian Kegawatdaruratan Di Rumah Pada Penderita Gagal Ginjal Kronik - Dwi yanti; Eka Sri Wahyuningsih; Husni Hidayat (Awatara Publisher, 2023)
The incidence of kidney failure in the world in 2021 is 2 million people, Indonesia in 2020 is 1,602,059 people, West Java Province is 131,846 people and Cirebon Regency in 2018 is 614 people. Chronic renal failure can lead to emergency conditions such as metabolic acidosis, hyperkalemia, fluid overload, and uremic encephalopathy. The purpose of this study was to determine the relationship between efforts to monitor cardiorespiratory complaints by the family with the incidence of emergencies at home in patients with chronic kidney failure at Mitra Plumbon Hospital Cirebon. This type of research is quantitative with a descriptive correlational design with a cross sectional approach. The population is the entire family of patients with chronic kidney failure at Mitra Plumbon Hospital Cirebon as many as 4152 and the sampling technique using purposive sampling method as many as 98 people. Collecting data using a questionnaire. Bivariate analysis with chi square test (χ2) was conducted in June 2022. The results showed that more than half (67.3%) of respondents did not make efforts to monitor cardiorespiratory complaints and more than half (69.4%) of respondents experienced an emergency. The results of the chi square test showed a relationship between efforts to monitor cardiorespiratory complaints by the family and the incidence of emergencies at home in patients with chronic kidney failure at Mitra Plumbon Hospital Cirebon (ρ = 0.000, = 0.05) Nurses are expected to provide education regarding monitoring of cardiorespiratory complaints in families of patients with chronic kidney failure.